Pengaruh Promosi Media Sosial Dan Daya Tarik Wisata Terhadap Minat Berkunjung Kembali Di Obyek Wisata Edukasi Manyung - Budi Susanto; Puji Astutik (Universitas Kadiri, 2020)
This study aims to determine the relationship of semester achievement index with student achievement and the relationship of cumulative achievement index with student achievement at the Faculty of Economics, Kadiri University. The technique of taking in the form of distributing questionnaires to students who were sampled by the method of purposive sampling was taken 100 respondents. In analyzing the data using the Chi-Square test to determine the relationship between variables. The results show that the Semester Achievement Index has a close relationship with student achievement with Cramer's V value of 0.556 and Contingency of 0.806 as evidenced by the value in Approx. Sig <0.05. Then the Cumulative Achievement Index has a close relationship with student achievement with Cramer's V value of 0.810 and Contingency of 0.893 as evidenced by the value in Approx. Sig <0.05Â Penelitian bertujuan mengetahui pengaruh promosi media sosial dan daya tarik wisata terhadap minat berkunjung kembali di obyek wisata edukasi Manyung. Sampel yang diambil dalam penelitian ini sebanyak 100 responden yang merupakan pengunjung atau wisatan di obyek wisata edukasi Manyung. Metode analisis data menggunakan regresi linear berganda. Hasil penelitian menunjukkan bahwa promosi media sosial berpengaruh positif dan signifikan dan daya tarik wisata juga berpengaruh secara signifikan terhadap minat berkunjung kembali di obyek wisata edukasi Manyung.